Gender Identity Construction in Relation to Prolonged Existence of Nancy Drew and Detective Conan as Mass Media (NOBEL: Journal of Literature and Language Teaching, 2013)
Gender concepts have developed through centuries. In capitalism era, it goes along with the development of media. Media plays an important role in social construction and supporting the ideology; it is also included in politics of representation. Through media, the depictions about gender role are introduced. Nancy Drew and Detective Conan are two of many mass media that introduce gender subjectivity. As products of culture that have survived for many years in their countries, America and Japan, the two literatures must have successfully suited the societies‟ preference of gender concepts and supported its construction at the same time. This paper analyzes how the development of gender concepts runs together with the prolonged existence of the two media and the role of both in supporting the ideology. The analysis will be begun with the discussion about their similarities and differences then cultural and historical background that underlie their survival as influencing mass media and the constructions that follow.